Implementation of Social Capital in The Management of Boarding School Economic Business Units - Akbar, Muhammad Rafli; Malik , Anas; Saefurrohmah, Ghina Ulfa (Golden Ratio of Social Science and Education, 2025)
This study aims to examine in depth the implementation of social capital in the management of economic business units at Al-Hikmah Islamic Boarding School in Bandar Lampung, as well as to analyze the economic self-reliance strategies employed to build a sustainable pesantren (Islamic boarding school) economic system. Utilizing a descriptive qualitative approach, data were collected through in-depth interviews, participatory observation, and document analysis involving various stakeholders, including both internal (administrators, students, and alums) and external (local community, students’ parents) parties, as well as third parties (developers of the Pesantren Smart Digital application, or PSD). The research findings indicate that the implementation of social capital, particularly trust, shared norms, and bridging social capital, plays a crucial role in creating an inclusive, transparent, and integrated pesantren economic governance system. Trust is established through a digital transaction system managed via the Pesantren Smart Digital (PSD) application, which not only ensures a secure and accountable financial flow for students but also strengthens oversight by both parents and pesantren administrators. This economic system is reinforced through the establishment of disciplinary regulations such as daily spending limits and the mandatory use of official receipts, along with strict sanctions for violations, serving as a form of norm-based social control. The pesantren's economic self-reliance strategies are also systematically developed through the formation of a dedicated economic division, the restructuring of business units such as SanNumart and SanNuairminum, the active involvement of students and alumni in business activities, and collaboration with the surrounding community and professional entities. As a result, the pesantren emerges not only as a religious educational institution but also as a center for community-based Islamic economic empowerment.